Forecast combination in the frequency domain - Gonçalo Faria; Fabio Verona (Bank of Finland, 2023)
Predictability is time and frequency dependent. We propose a new forecasting method - forecast combination in the frequency domain - that takes this fact into account. With this method we forecast the equity premium and real GDP growth rate. Combining forecasts in the frequency domain produces markedly more accurate predictions relative to the standard forecast combination in the time domain, both in terms of statistical and economic measures of out-of-sample predictability. In a real-time forecasting exercise, the flexibility of this method allows to capture remarkably well the sudden and abrupt drops associated with recessions and further improve predictability.
Keywords: C58; G11; G17; 330; forecast combination; frequency domain; equity premium; GDP growth; Haar filter; wavelets